1975
DOI: 10.1159/000119593
|View full text |Cite
|
Sign up to set email alerts
|

Cerebral Fluid Dynamics and Brain Regional Blood Flow in Experimental Hydrocephalus

Abstract: Cerebral blood flow was measured by the indicator fractionation technique in normal, acute hydrocephalic, chronic compensated hydrocephalic and craniectomized hydrocephalic cats. In the five normal cats the mean total brain blood flow was 136.1 ml/min/100 g dry weight. The six acute hydrocephalic animals demonstrated a relatively uniform 22% reduction in total blood flow. In eight chronic hydrocephalic cats CBF increased to the point where there was only an overall 7% decrease. In three hydrocephalic and crani… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

1986
1986
2019
2019

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 0 publications
0
10
0
Order By: Relevance
“…Both clinical 2,24,61 and experimental 23,27,34,35,47,5z studies have established that hydrocephalus is associated with a reduction in cerebral blood flow (CBF), although not to levels considered low enough to cause cerebral ischemia. 7~ Previous work from this laboratory using a neonatal kitten model of hydrocephalus has confirmed the presence of cerebral hypoperfusion and has shown changes on magnetic resonance (MR) spectroscopy consistent with mild cerebral ischemia and delayed myelination (unpublished data).…”
mentioning
confidence: 99%
“…Both clinical 2,24,61 and experimental 23,27,34,35,47,5z studies have established that hydrocephalus is associated with a reduction in cerebral blood flow (CBF), although not to levels considered low enough to cause cerebral ischemia. 7~ Previous work from this laboratory using a neonatal kitten model of hydrocephalus has confirmed the presence of cerebral hypoperfusion and has shown changes on magnetic resonance (MR) spectroscopy consistent with mild cerebral ischemia and delayed myelination (unpublished data).…”
mentioning
confidence: 99%
“…Although most studies have described cerebrovascular compression in CH (Del Bigio and Bruni, 1988), a few studies have observed increased vascular density in certain brain regions and at various time points in CH (Dombrowski et al, 2008;Luciano et al, 2001;Ransohoff et al, 1975). Previously, we have shown an initial decrease in vascularity followed by a return above baseline in cortical gray and periventricular white matter in CH .…”
Section: Introductionmentioning
confidence: 76%
“…Compression of capillaries, also called cerebrovascular compression, plays a significant role in the acute stage. Various research studies have confirmed collapse of cerebral capillaries in the periventricular white matter and cortical and subcortical gray matter [154][155][156][157][158]. Changes of cerebral circulation, which are adaptive in their nature, also known as cerebrovascular adaptation, occur in the chronic stage of hydrocephalus.…”
Section: Vascular Changes In Hydrocephalusmentioning
confidence: 99%